Community‐Level Exposure to the Rural Mining Industry: The Potential Influence on Early Adolescent Alcohol and Tobacco Use. Issue 3 (31st January 2018) - Gay, Christopher; Clements‐Nolle, Kristen; Packham, John; Ackerman, Gerald; Lensch, Taylor; Yang, Wei
Abstract: Purpose: Rural youth have higher rates of alcohol and tobacco use compared to their urban counterparts. However, the economic dependence of rural communities may differentially influence risk behaviors. While research has shown that adults working in mining have elevated rates of alcohol and tobacco use, the influence of living in a mining community on early adolescent substance use is unknown. Methods: Using data from a representative sample of 4, 535 middle school students in a state with heavy reliance on mining, we conducted weighted logistic regression to investigate whether community‐level mining economic dependence influences rural‐urban differences in adolescent alcohol and tobacco use. All models adjusted for sociodemographics, military family involvement, parental monitoring, and length of residence. Findings: Over one quarter of the sampled students lived in rural counties and approximately half of these counties met the USDA mining economic typology. After stratifying rural counties by mining and nonmining economic dependence, students in rural mining counties had significantly higher odds of all measures of alcohol use (AORs ranged from 1.83 to 3.99) and tobacco use (AORs ranged from 1.61 to 5.05) compared to students in urban counties. Only use of smokeless tobacco was higher among students in rural nonmining counties. Conclusions: Our findings demonstrate rural‐urban disparities in adolescent substance use that are particularly pronounced among youth living in counties with economic dependence on mining. Future research on this subject should include a wider range of community‐level factors that may have specific relevance in rural settings to inform the development of population‐level interventions.